1996
DOI: 10.1002/(sici)1099-1077(199601)11:1<47::aid-hup743>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicotine in visual attention tasks

Abstract: Thirty-five male volunteers (18 nicotine-users and 17 controls) participated in an experiment where a flanker task and a search task were used. It was hypothesized that if nicotine affects selective attention, the effects of distracting flanker stimuli should be diminished, and effects of allocation strategies in the search task should be more marked. Nicotine-users performed the tasks after an overnight abstinence, and after administration of oral snuff. In both tasks nicotine users improved more than control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As discussed previously, test performance that is impaired after tobacco deprivation appears to be reliably reversed to smoking baseline levels (cf., Heishman et at., 1994), whereas performance that is not degraded by deprivation may be more likely to be enhanced by smoking (Baldinger et aI., 1995). In healthy nonsmokers or non-deprived smokers, studies have generally reported no enhancing effect of nicotine or smoking on tests of selective attention (Foulds et al, 1996;Heishman et al, 1993;Lindgren, Stenberg, & Rosen, 1996;Parrott & Craig, 1992;Spilich, June, & Renner, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed previously, test performance that is impaired after tobacco deprivation appears to be reliably reversed to smoking baseline levels (cf., Heishman et at., 1994), whereas performance that is not degraded by deprivation may be more likely to be enhanced by smoking (Baldinger et aI., 1995). In healthy nonsmokers or non-deprived smokers, studies have generally reported no enhancing effect of nicotine or smoking on tests of selective attention (Foulds et al, 1996;Heishman et al, 1993;Lindgren, Stenberg, & Rosen, 1996;Parrott & Craig, 1992;Spilich, June, & Renner, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…These kind of changes may result from increased attentional focus and /or mental e¦ciency (Edwards et al 1985), or they could result from increased cortical arousal (Knott 1985;Cinciripini 1986;Lindgren 1996). Desynchronization of the spontaneous activity of cells in the cortex may represent one such mechanism of arousal, which might lead to increased excitability, making the system more sensitive to incoming stimuli and resulting in enhanced cortical evoked potentials.…”
Section: E¤ects On Cortical Electrophysiologymentioning
confidence: 99%
“…Regarding interference control, one study reported more efficient executive control with a nicotine patch in the ANT (AhnAllen et al 2008). Another study observed an overall reduction in reaction time and an improvement in correct response rate in smokers following oral snuff (Lindgren et al 1996), but there are also failures to observe nicotine effects on the flanker task (Lindgren et al 1996;Kleykamp et al 2005;Wignall and De Wit 2011;Myers et al 2013).…”
Section: Introductionmentioning
confidence: 99%